2013
DOI: 10.1093/gbe/evt058
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recurrent Mutations in the Human Mitochondrial Phylogeny: Dual Roles in Evolution and Disease

Abstract: Mutations frequently reoccur in the human mitochondrial DNA (mtDNA). However, it is unclear whether recurrent mtDNA nodal mutations (RNMs), that is, recurrent mutations in stems of unrelated phylogenetic nodes, are functional and hence selectively constrained. To answer this question, we performed comprehensive parsimony and maximum likelihood analyses of 9,868 publicly available whole human mtDNAs revealing 1,606 single nodal mutations (SNMs) and 679 RNMs. We then evaluated the potential functionality of syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 65 publications
2
55
0
1
Order By: Relevance
“…Since the analyzed samples are part of the 1000 Genomes Project, we extracted the mtDNA sequence from the DNA sequence database of the same samples and used these to construct a phylogenetic tree (S3B Fig). Notably, the topologies and distribution of haplogroups throughout the RNA and DNA-based trees were nearly identical and were in agreement with previously published trees [12, 36]. Therefore, putative human RNA-DNA sequence differences did not affect overall mtDNA tree topology.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Since the analyzed samples are part of the 1000 Genomes Project, we extracted the mtDNA sequence from the DNA sequence database of the same samples and used these to construct a phylogenetic tree (S3B Fig). Notably, the topologies and distribution of haplogroups throughout the RNA and DNA-based trees were nearly identical and were in agreement with previously published trees [12, 36]. Therefore, putative human RNA-DNA sequence differences did not affect overall mtDNA tree topology.…”
Section: Resultssupporting
confidence: 89%
“…However, accumulating evidence suggests that many common variants in the mitochondrial and nuclear genomes have functional impacts [3]. Specifically, ancient mitochondrial DNA (mtDNA) variants and genetic backgrounds (haplotypes, haplogroups) have been associated with an altered tendency to develop a variety of complex traits [35] that affected mitochondrial activity in cell culture experiments [69] and which conferred adaptive advantages over the course of human evolution [1012]. Whereas it has been shown that mtDNA variants affected mitochondrial protein activities, such as oxidative phosphorylation (OXPHOS) or the production of reactive oxygen species (ROS), the impact of mtDNA variants on the regulation of gene expression has drawn little attention.…”
Section: Introductionmentioning
confidence: 99%
“…The human genus Homo separated from its higher primate ancestry about 6 million years ago (44), (45). Over this interval, several species evolved with Homo sapiens appearing about 300,000 years ago(46), (47), which is now regarded as the modern human. The origin of human DNA variation is primarily due to DNA copying errors during replication of the two strands of DNA (48), (49).…”
Section: Genetic Risk Variants Confirm the Long Suspected Genetic Prementioning
confidence: 99%
“…Between 200 000 to 300 000 years ago, the homo sapiens emerged, referred to as the modern human species, and migrated out of Africa between 120 000 and 150 000 years ago. 31,32 Throughout this long evolutionary interval, despite most DNA sequences being similar across genii and species, sequences unique to each species were maintained. Throughout the homo sapiens species, the DNA sequence is 99.5% identical with 0.5% or 15 million base pairs being different.…”
Section: Evolution Of Human Dna Variationmentioning
confidence: 99%